Estimating Soil Loss for Sustainable Crop Production in the Semi-deciduous Forest Zone of Ghana - Sekyi-Annan, Ephraim; Gaisie, Ekow; Issaka, Roland Nuhu; Quansah, Gabriel Willie; Adams, Sadick; Bessah, Enoch (Frontiers in Sustainable Food Systems, 2021)
Quantitative information on soil loss is relevant for devising soil conservation and crop management strategies to ensure sustainable fertility management and crop production. Estimations from runoff/erosion plots are expensive and laborious and thus requiring the exploration of other less expensive but reliable methods such as modeling. This study aimed to estimate current and future rates of soil loss for conservation planning toward sustainable crop production in the semi-deciduous forest zone of Ghana. The Universal Soil Loss Equation (USLE), which took into consideration the rainfall characteristics of the study area, inherent soil physicochemical and hydraulic properties, variations in slopes and terrain differences, land cover types, and soil management practices, was employed to estimate the magnitude and rate of soil loss in the study area. Output from three regional climate models (RCMs) from Coordinated Regional Climate Downscaling Experiment including CCCma-CanESM2, GFDL-ESM2M, and HadGEM2-ES were used to estimate the impact of climate change on soil erosion in the study area. The results showed that soil loss estimated for bare soils was high ranging from 12.7 to 163.8 t ha−1 year−1 largely due to variation in slopes coupled with soil physicochemical and hydraulic properties. The simulated annual soil losses under various land cover options showed variable degrees of soil loss for maize cultivation under conventional tillage (8.2–106.5 t ha−1 year−1), soya bean monocropping (4.4–57.3 t ha−1 year−1), and low soil loss for oil palm plantation with grass or leguminous cover (2.5–32.8 t ha−1 year−1). Evaluation of the RCMs showed excellent performance for CCCma-CanESM2 and GFDL-ESM2M. Predictions of climate change impact using outputs from CCCma-CanESM2 and GFDL-ESM2M indicated that 9–39% increase in soil loss is expected by 2070, and it will be more severe (16–42%) by 2100. The model predictions indicate that the adoption of site-specific land cover management strategies such as tree–cover crop intercropping and reduced tillage has a huge potential to reduce soil loss and sustain soil fertility. The model can be used as an advisory tool for mapping areas for appropriate cropping systems for a particular site.